(untitled) (ModaPalavra e-periódico, 2023)
Market segmentation consists of defining sociodemographic and consumption attributes of potential customers of a company/brand. These elements will guide product development and marketing actions. Considering the scope of the Fashion industry, such segmentations are strictly necessary as organizations manage to devise strategies and deliver quality products and experiences. In this context, one of the contemporary strategies is using digital influencers (DI) to generate value for the customer. Such endorsements can be explained from four dimensions: reliability, experience, style/attractiveness, and parasocial relationship. Thus, this paper aims to propose a segmentation based on these dimensions and how they intersect with the purchase intention endorsed by DI. With that, 103 individuals were questioned, and the k-means clustering technique was used to generate consumption groups. It was possible to perceive three groups, called: “sweet and sassy,” “perfect rhythm,” and “involving,” with low, medium, and high purchase intention, respectively.